2016
DOI: 10.1002/jsfa.8054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reciprocating agitation thermal processing (RA‐TP) on quality of canned tomato (Solanum lycopersicum) puree

Abstract: Research findings indicate that RA-TP can be effective to obtain thermally processed foods with high-quality attribute retention. It can also be concluded that a very high reciprocation frequency (>3 Hz) is not necessarily needed and significant quality improvement can be obtained at lower frequencies (∼2 Hz). © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Improvements in process time were also observed in a canned tomato puree processed in a vertical steam reciprocating retort. The process time decreased from 43.4 min under static conditions to 8.1 min at 3 Hz, which is equivalent to 180 SPM (Singh et al, 2017). Overall, reciprocal agitation technology provided shorter process time than static retorts at all agitation speeds for process time and achieving target F 0 value.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Improvements in process time were also observed in a canned tomato puree processed in a vertical steam reciprocating retort. The process time decreased from 43.4 min under static conditions to 8.1 min at 3 Hz, which is equivalent to 180 SPM (Singh et al, 2017). Overall, reciprocal agitation technology provided shorter process time than static retorts at all agitation speeds for process time and achieving target F 0 value.…”
Section: Resultsmentioning
confidence: 88%
“…When come-up-time credit was considered during cook (P t ), only three of the four agitation speeds had higher general method cook times than the Ball's formula method at a F 0 value of 3.5. Overall, the processor could reduce the cook time by 2 to 4 min to achieve an F 0 of 3.5; the reduced time at retort temperature can have a significant impact on improving product quality (Stoforos, 2010;Erdogdu et al, 2016;Singh et al, 2017Singh et al, , 2018.…”
Section: Spm Initial Parametersmentioning
confidence: 99%
“…However, long‐term storage might cause losses in thiamin (Rickman, Barrett, & Bruhn, 2007). In a study by Pratap Singh et al (2017), antioxidant activity decreased regardless of the reciprocation or still retorting. However, total phenols increased with reciprocating retort processing, particularly with high‐frequency reciprocation.…”
Section: Nutritional Datamentioning
confidence: 94%
“…The degradation increases with the degree of damage to the cellular structure of the raw material, an increase in the surface available for the influence of external factors, the time and conditions of storage, and exposure to light and oxygen (Rodriguez‐Amaya, 2016). Multiple authors (Barba et al., 2017; Pratap Singh et al., 2017, 2020) found that heat treatment can often cause significant loss of carotenoids; however, moderate heat treatment results in bioavailability growth. Increased bioavailability has been attributed to the fact that thermal processing disrupts cell matrix due to mechanical homogenization, resulting in better absorption, yet severe heat treatment such as sterilization may reduce bioavailability (Pratap Singh et al., 2017).…”
Section: Characteristics Of Natural Pigments In Plant Tissuementioning
confidence: 99%
“…Multiple authors (Barba et al., 2017; Pratap Singh et al., 2017, 2020) found that heat treatment can often cause significant loss of carotenoids; however, moderate heat treatment results in bioavailability growth. Increased bioavailability has been attributed to the fact that thermal processing disrupts cell matrix due to mechanical homogenization, resulting in better absorption, yet severe heat treatment such as sterilization may reduce bioavailability (Pratap Singh et al., 2017). In contrast, nonthermal processing caused no or very little loss (Barba et al., 2017).…”
Section: Characteristics Of Natural Pigments In Plant Tissuementioning
confidence: 99%